Neural and Genetic Bases for Human Ability Traits - Pinto, Camila Bonin; Bielefeld, Jannis; Jabakhanji, Rami; Reckziegel, Diane; Griffith, James W.; Apkarian, A. Vania (Frontiers in Human Neuroscience, 2020)
The judgement of human ability is ubiquitous, from school admissions to job performance reviews. The exact make-up of ability traits, however, is often narrowly defined and lacks a comprehensive basis. While personality domains have been extensively studied, human ability has not received the same attention. Finding a basis for human ability would be invaluable since neuropsychiatric disease diagnoses and symptom severity are commonly related to such differences in performance. Here, we identified four underlying ability traits within the National Institutes of Health Toolbox normative data (n = 1369): 1: Motor-endurance, 2: Emotional processing, 3: Executive and cognitive function, and 4: Social interaction. We used the Human Connectome Project young adult dataset (n = 778) to show that Motor-endurance and Executive and cognitive function were reliably associated with specific brain functional networks (r^2=0.305±0.021), and the biological nature of these ability traits was also shown by calculating their heritability (31% and 49% respectively) from twin data.